Assessment of the fundamentals of failure theories for composite materials - Talreja, Ramesh (Composites science and technology, 2014)
Failure theories for composite materials have been a subject of concern for almost half a century. Numerous theories have been proposed over the years, but none of them has successfully predicted the full range of observed behavior. This paper critically reviews some of the main theories in an effort to understand their deficiencies. Rather than seek their validity by comparison with test data, the assumptions and analyses underlying the proposed theories are examined. Certain remedies are proposed to the current approaches to achieve a failure analysis procedure with a potential to succeed in predicting the complex failure behavior of composite materials.